Wave and Knowledge in Alivin Toffler's Thinking - ميا, ماري; هلا علي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The American thinker Alvin Toffler discusses civil waves that divided the history of human development into three waves; the agricultural wave, the industrial wave, and the knowledge wave. Toffler believes that the emergence of each of these waves was associated with new patterns of knowledge. Therefore, the knowledge that generated agriculture is different from the knowledge that generated industry. It is also primative compared to it. The same applies to the knowledge that generated the third wave which considers the industrial wave primitive. Toffler emphasises the effect of the three waves on all aspects of life, which in turn will affect each individual in the society. Families are deconstructed, economy is destructed, political systems are paralyzed and values are ignored. Toffler also confirmed the disturbance accompanying each of these waves; where the presence of the third wave caused a social rage that whole humanity undergoes as the values of the new civilization contradict the old industrial civilization. It also presents advanced technologies oppose the industrial movement. In addition to that, each wave holds conflicts that differ from those of the previous and the following ones. As a result, Toffler talks about not going back to old conflicts since each development imposes both advanced knowledge and conflicts.